An Experience of Management of Parapharyngeal Space Tumours - MOHAMMAD JAVAID QAISAR KHAN, NIAMATULLAH (Journal of Fatima Jinnah Medical University, 2018)
Objective: To determine the clinical presentation and management of parapharyngeal space tumours at a tertiary care hospital. Patients and Methods: All the patients with diagnosis of parapharyngeal space presented to Department of ENT, Head and Neck surgery, Postgraduate Medical Institute (PGMI), Lady Reading Hospital (LRH), Peshawar-Pakistan were included in this study. After taking detailed history, thorough examination was carried out and relevant investigations were performed. These patients were operated and were disease free. Results: Ninety one percent of the parapharyngeal space neoplasms were benign; 9% were malignant. Majority of the benign tumors were salivary gland origin followed by neurogenic tumors. The use of FNAC, computed tomography scan and ultrasound imaging are very useful to assess the location, size, vascularity, tissue origin and relation of parapharyngeal space tumors to surrounding anatomical structures. Conclusion: This information was essential in planning surgical approaches and predicting the prognosis. Details of the management, morbidity, and outcome of these patients were presented.